Pendidikan Karakter Mempengaruhi Pembentukan Kejujuran Siswa MTs Negeri 1 Lombok Barat - Endang Kartini; Izrawati Izrawati; Lalu Mimbar (Sekolah Tinggi Ilmu Ekonomi AMM, 2020)
This study aims to: Know character education as measured by religion, personality, environment, and nationality partially (individually) and significantly influence the formation of honesty of MTs.NI students in West Lombok. Know character education as measured by (religious, personality, environment, and nationality) simultaneously (saama-sama) and significant influence on the formation of honesty of MTs.NI students in West Lombok. Knowing which subvariables are the most dominant influences the honesty of MTs.N I West Lombok students. Knowing the influential independent subvariable, how much does it contribute to the formation of honesty students in MTs.N I West Lombok. The population of all students in class VIII is 176 people. The research sample of 64 respondents consisted of class VIII.A = 9 people, VIII.B = 11 people, class VIII.C = 11 people, class VIII.D = 11 people, class VIII.E = 11 people, and class VIII. F = 11 people, with the calculation described in Chapter III. The results showed that Character Education as measured by religion, personality, environment, and nationality had a significant and positive effect on the formation of honesty of students in MTs.N 1 West Lombok. Simultaneously, the variables of religious Character, Personality Character, Environmental Character, and National Character have a significant effect on the Formation of Student Honesty, this can be seen from the calculated F value greater than the F table where the F count is 41,966 and the F table is 2.37 (41. 966 > 2.37). MTs.N 1, West Lombok in general can meet students 'expectations both in terms of the evidence that has been stressed on each student, students' responsiveness to the delivery of religious values, and empathy. The next variable that also influences the formation of students' honesty is personality character. The next two variables, namely the character of the environment, and national character, in general, can create confidence for the formation of honesty, including good students, with good perceptions that arise, resulting in the emergence of moral values ​​for students of MTs.N 1 Lombok Barat